Nursery Rearing of Nonhuman Primates in the 21st Century - Sackett, Gene P.; Ruppenthal, Gerald; Elias, Kate (Developments in Primatology: Progress and Prospects,, 2006)
Nursery Rearing of Nonhuman Primates in the 21st Century describes how and why nursery rearing of primates can produce adaptable juveniles and adults for research, conservation, and display-educational purposes. The volume details the history of nursery rearing since the mid-19th century, the outcomes of varied nursery rearing methods, the contemporary goals of nursery rearing as well as reference data derived from species commonly reared in nursery or hand-feeding situations. Examples of the changing goals of nursery rearing covered in this volume are the need for biological containment in disease research, the production of specific pathogen-free colonies by removal of neonates from the mother, the production of phenotypes for genetic and molecular biology studies, and the breeding of endangered species for conservation or research purposes.